Question about Super Tutor Trigonometry (ESDTRIG) for PC

1 Answer

Help sec^4X- sec^2X = 1/cot^4X + 1/cot^2X

Posted by on

1 Answer

  • Level 2:

    An expert who has achieved level 2 by getting 100 points

    MVP:

    An expert that got 5 achievements.

    Vice President:

    An expert whose answer got voted for 100 times.

    Governor:

    An expert whose answer got voted for 20 times.

  • Expert
  • 139 Answers

Sec^4X- sec^2X = 1/cot^4X + 1/cot^2X
RHS
1/cot^4X + 1/cot^2X
=1/(Cos^4X/Sin^4X) + 1/(Cos^2X/Sin^2X)
=Sin^4X/Cos^4X + Sin^2X/Cos^2X
=Sin^4X/Cos^4X + Cos^2X.Sin^2X/Cos^4X
=Sin^2X/Cos^4(Sin^2X + Cos^2X)
=Sin^2X/Cos^4X
=(1-Cos^2X)/Cos^4X
=1/Cos^4X - Cos^2X/Cos^4X
=1/Cos^4X - 1/Cos^2X
=Sec^4X - Sec^2X
=LHS

Posted on Mar 15, 2009

×

1 Suggested Answer

6ya6ya
  • 2 Answers

SOURCE: I have freestanding Series 8 dishwasher. Lately during the filling cycle water hammer is occurring. How can this be resolved

Hi,
a 6ya expert can help you resolve that issue over the phone in a minute or two.
best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.
the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).
click here to download the app (for users in the US for now) and get all the help you need.
goodluck!

Posted on Jan 02, 2017

Add Your Answer

Uploading: 0%

my-video-file.mp4

Complete. Click "Add" to insert your video. Add

×

Loading...
Loading...

Related Questions:

1 Answer

How do I solve (3x-2y)2(3xy-3)


First, we will find y in terms of x. We will use the first equation to determine this.
4x+2y=2
We can subtract 4x from both sides:
2y=2-4x
And then divide both sides of the equation by two:
y=1-2x
Since we now have y in terms of x, we can substitute this into our second equation.
-3x-y=-3
-3x-(1-2x)=-3
Then, we can distribute the minus sign
-3x-1+2x=-3
-x-1=-3
Next, we can add 1 to both sides of the equation.


-x=-2
Finally, we divide both sides by negative one to isolate x.
x=2
Now that we have x's value, we can find y's value.
The first thing that we determined is:
y=1-2x
We can substitute in the value of x to this equation.
y=1-2x
plot-formula.mpl?expression=y=1-2%2a2&x=0003
y=1-4
y=-3
Therefore, we now have the values of both variables.
x=2
y=-3

Jan 13, 2015 | SoftMath Algebrator - Algebra Homework...

1 Answer

What is rational expression of (22x +11) (10x2 +5x)


I assume the 10x2 means 10 squared. (I will show it as 10x**2)
(22x+11)(10x**2+5x) factors into"
11(2x+1)*5(2x**2+1x)
=55(2x+1)(2x**2+1x)
=(55x)(2x+1)(2x+1)
Multiplied out, it becomes 55x(4x**2+4x+1)
= 220x**3 + 220x**2 + 55x

Dec 11, 2014 | Computers & Internet

1 Answer

Csc(x)cot(x)/sec(x)


csc(x)=1/sin(x)
sec(x)=1/cos(x)
csc(x)/sec(x)=(1/sin(x))*(cos(x)=cot(x)
csc(x)*cot(x)/sec(x)=(cot(x))^2=(tan(x))^(-2)

Jul 12, 2014 | Super Tutor Trigonometry (ESDTRIG) for PC

1 Answer

2(3-x)+3(x-1)=4x


x equals 1

First multiply the numbers outside the parentheses by what is inside the parentheses, which results in:

6 - 2x + 3x - 3 = 4x

then combine what you can:

6 - 3 = 3,
-2x + 3x = 1x

which leaves:

3 + x = 4x

Subtract the x on the left from the 4x on the right and you get:

3 = 3x

Divide by 3 to get the x alone

3 / 3 = 1

x = 1

Feb 02, 2014 | SoftMath Algebrator - Algebra Homework...

1 Answer

4x - 2x + 1 = 5 + x - 7


1. Combine like terms on the left side of =

4x-2x =2x

New left side is 2x + 1

2. Combine like terms on right side of =

5 - 7 = -2

New right side is x - 2

3. New problem is 2x + 1 = x - 2

4. Now get all x terms on left side of =
and all constants on right side of = by adding the opposites of the corresponding terms as you move them across the =

2x - x = -2 - 1

5. Combine the like terms on each side of the =

Left side: 2x - x = x and Right side: -2 -1 = -3

So x = -3

6. Now check your solution by substituting your answer back in to the original problem.

4(-3) - 2(-3) + 1 = 5 + (-3) -7

7. Now do the arithmatic and hopefully the left and right sides are equal.

-12 + 6 +1 = 5 -3 -7
-5 = -5

Since this is a true statement I know my answer of x = -3 is the correct solution to this problem.

May 17, 2012 | SoftMath Algebrator - Algebra Homework...

2 Answers

4x-(2x-3)=0


4x-(2x-3)=0
=>4x-2x+3=0 ; (after the bracket's oepned and multiplied by - [minus])
=>2x+3=0 ; taken x as common and 4-2=2 i.e. x(4-2) = 2x
=>2x=-3 ; +3's moved on the right-hand side, so it becomes -3
=>x=-3/2 ; 2 has been moved to the right-hand side and divided with -3 i.e 1/2 multiplied by -3 = -3/2

Hence, x = -3/2


Good luck.

Thanks for using FixYa.

Aug 13, 2010 | SoftMath Algebrator - Algebra Homework...

1 Answer

. x^3 - 4x^2 - 12x


Hii,you can use the following solution x^3 - 4x^2-12x=0 x(x^2-4x-12)=0 replacing -4x from -6x+2x x(x^2-6x+2x-12)=0
Now Factoring x(x(x-6) +2(x-6))=0 x(x-6)(x+2)=0 Solution is x=0, x-6=0,x+2=0 1) x=0 2) x-6=0 =>x=6 3) x+2=0 =>x=-2

May 05, 2010 | Vivendi Excel@ Mathematics Study Skills...

1 Answer

(1+cotx-cosecx)(1+tanx+secx)=2


I shall attempt :D
1) cosec A + cot A = 3
we know that (cot A)^2 + 1 = (cosec A)^2
Hence, (cosec A)^2 - (cot A)^2 = 1
thus, (cosec A + cot A) (cosec A - cot A) = 1
3 (cosec A - cot A) = 1
(cosec A - cot A) = 1/3

(cosec A - cot A) = 1/3
(cosec A + cot A) = 3
Summing them, 2 cosec A = 3 1/3
cosec A = 6 2/3 = 5/3
sin A = 0.15
Thus, cos A = sqrt (1 - (sin A)^2) = 0.989


2) Prove that (1+tan x - sec x)(1 + cot x + cosec x) =2
expand
LHS= 1 + cot x + cosec x + tan x + 1 + tan x cosec x - sec x - sec x cot x - sec x cosec x
We can calculate that
tan x cosec x = sec x (since tan x = sin x / cos x)
sec x cot x = cosec x
so the above is
LHS = 1 + cot x + cosec x + tan x + 1 + sec x - sec x - cosec x - sec x cosec x
LHS = 2 + cot x + tan x - sec x cosec x
LHS = 2 + cos x / sin x + sin x / cos x - 1 / (sin x cos x)
LHS = 2 + [{cos x}^2 + {sin x}^2 - 1] / (sin x cos x)
LHS = 2 (proved)

May 12, 2009 | ValuSoft Bible Collection (10281) for PC

1 Answer

4x+8y=20 -4x+2y=-30


4x+8y=20 || /4
x+2y=5
x=5-2y

-4x+2y=-30 || /2
-2x+y=-15
-2(5-2y)+y=-15
-10+4y+y=-15
5y=-5
y=-1

x=5-2y || y=-1
x=5-2(-1)
x=5+2
x=7

Mar 10, 2009 | Bagatrix Algebra Solved! 2005 (105101) for...

5 Answers

Algebra 1


B. 2((2-Y)/3)-Y=3
2(2-Y)-Y=9
4-2Y-Y=9
-3Y=9-4
-3Y=5
-Y=5/3
Y=-1.67

A. 3X+(-1.67)=2
3X-1.67=2
3X=2+1.67
3X=3.67
X=3.67/3
X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

Not finding what you are looking for?
Computers & Internet Logo

Related Topics:

489 people viewed this question

Ask a Question

Usually answered in minutes!

Top Super Tutor Computers & Internet Experts

k24674

Level 3 Expert

7993 Answers

kakima

Level 3 Expert

98879 Answers

cwradio73

Level 3 Expert

899 Answers

Are you a Super Tutor Computer and Internet Expert? Answer questions, earn points and help others

Answer questions

Manuals & User Guides

Loading...